Celecoxib ameliorates diabetic sarcopenia by inhibiting inflammation, stress response, mitochondrial dysfunction, and subsequent activation of the protein degradation systems - Deng, Chunyan; Lu, Chunfeng; Wang, Kexin; Chang, Mengyuan; Shen, Yuntian; Yang, Xiaoming; Sun, Hualin; Yao, Xinlei; Qiu, Chunjian; Xu, Feng (Frontiers in Pharmacology, 2024)
Aim: Diabetic sarcopenia leads to disability and seriously affects the quality of life. Currently, there are no effective therapeutic strategies for diabetic sarcopenia. Our previous studies have shown that inflammation plays a critical role in skeletal muscle atrophy. Interestingly, the connection between chronic inflammation and diabetic complications has been revealed. However, the effects of non-steroidal antiinflammatory drug celecoxib on diabetic sarcopenia remains unclear. Materials and Methods: The streptozotocin (STZ)-induced diabetic sarcopenia model was established. Rotarod test and grip strength test were used to assess skeletal muscle function. Hematoxylin and eosin and immunofluorescence staining were performed to evaluate inflammatory infiltration and the morphology of motor endplates in skeletal muscles. Succinate dehydrogenase (SDH) staining was used to determine the number of succinate dehydrogenase-positive muscle fibers. Dihydroethidium staining was performed to assess the levels of reactive oxygen species (ROS). Western blot was used to measure the levels of proteins involved in inflammation, oxidative stress, endoplasmic reticulum stress, ubiquitination, and autophagic-lysosomal pathway. Transmission electron microscopy was used to evaluate mitophagy. Results: Celecoxib significantly ameliorated skeletal muscle atrophy, improving skeletal muscle function and preserving motor endplates in diabetic mice. Celecoxib also decreased infiltration of inflammatory cell, reduced the levels of IL-6 and TNF-α, and suppressed the activation of NF-κB, Stat3, and NLRP3 inflammasome pathways in diabetic skeletal muscles. Celecoxib decreased ROS levels, downregulated the levels of Nox2 and Nox4, upregulated the levels of GPX1 and Nrf2, and further suppressed endoplasmic reticulum stress by inhibiting the activation of the Perk-EIF-2α-ATF4-Chop in diabetic skeletal muscles. Celecoxib also inhibited the levels of Foxo3a, Fbx32 and MuRF1 in the ubiquitin-proteasome system, as well as the levels of BNIP3, Beclin1, ATG7, and LC3Ⅱ in the autophagic-lysosomal system, and celecoxib protected mitochondria and promoted mitochondrial biogenesis by elevating the levels of SIRT1 and PGC1-α, increased the number of SDH-positive fibers in diabetic skeletal muscles. Conclusions: Celecoxib improved diabetic sarcopenia by inhibiting inflammation, oxidative stress, endoplasmic reticulum stress, and protecting mitochondria, and subsequently suppressing proteolytic systems. Our study provides evidences for the molecular mechanism and treatment of diabetic sarcopenia, and broaden the way for the new use of celecoxib in diabetic sarcopenia.